Biodiversity of Termite (insecta: isoptera) in tropical peat land cultivated with oil palms - King, Patricia Jie Hung (2012)
Termites are the major decomposers in tropical region but yet their occurrences in oil palm plantation especially in peat soil are generally treated as pest. Study of termite species in peat land was conducted in selected oil palm plantations in North Sarawak with 5-7 years old palms and South Sarawak with 13-15 years old palms with two sites in each area. Results of quadrate (25x25x30 cm) sampling showed termite was significantly higher in relative density with increasing depth of soil (0-10 = 21.23, 10-20 = 42.52 and 20-30 cm = 81.12%) which could be advantaged from being predated by ants (Hymenoptera: Formicidae) which were higher in density from soil surface to 10 cm soil depth with relative density of 31.84%. Modified transect sampling (50x6 m) had successfully sampled 18 species of termites from 2 families (Rhinotermitidae and Termitidae), 5 subfamilies (Rhinotermitinae, Coptotermitinae, Termitinae, Macrotermitinae and Nasutitermitinae) and 11 genera (Coptotermes, Schedorhinotermes, Termes, Macrotermes, Nasutitermes, Globitermes, Amitermes, Parrhinotermes, Pericapritermes, Havilanditermes and Prohamitermes). Both plantation sites have termite dominantly feeding on rotten wood as a result of abundant dead woods. However, Coptotermes curvignathus Holmgren was identified to feed on the living tissues of oil palm causing damage or death of the tree. Study showed higher encounter of soil-feeding termite in longer established plantation. It indicates the gradually shifting of soil condition towards a stabilized environment which favors the successful settlement of soil feeder termite species. Termite control should be more targets specific to avoid harming beneficial termites.